Temporal and sequential transcriptional dynamics define lineage shifts in corticogenesis. (8th November 2022) - Mukhtar, Tanzila; Breda, Jeremie; Adam, Manal A; Boareto, Marcelo; Grobecker, Pascal; Karimaddini, Zahra; Grison, Alice; Eschbach, Katja; Chandrasekhar, Ramakrishnan; Vermeul, Swen; Okoniewski, Michal; Pachkov, Mikhail; et al.
Abstract: The cerebral cortex contains billions of neurons, and their disorganization or misspecification leads to neurodevelopmental disorders. Understanding how the plethora of projection neuron subtypes are generated by cortical neural stem cells (NSCs) is a major challenge. Here, we focused on elucidating the transcriptional landscape of murine embryonic NSCs, basal progenitors (BPs), and newborn neurons (NBNs) throughout cortical development. We uncover dynamic shifts in transcriptional space over time and heterogeneity within each progenitor population. We identified signature hallmarks of NSC, BP, and NBN clusters and predict active transcriptional nodes and networks that contribute to neural fate specification. We find that the expression of receptors, ligands, and downstream pathway components is highly dynamic over time and throughout the lineage implying differential responsiveness to signals. Thus, we provide an expansive compendium of gene expression during cortical development that will be an invaluable resource for studying neural developmental processes and neurodevelopmental disorders. Synopsis: Understanding brain development requires detailed insight into the temporal transcription dynamics associated with cell lineage determination. This genome‐wide profiling study provides a comprehensive transcriptomic resource of dorsal cerebral cortical lineages, highlighting the dynamics in gene expression from neural stem cells, basal progenitors, and newborn neurons at the population and single‐cell levels. Neural stem cells (NSCs), basal progenitors (BPs) and newborn neurons (NBN) of the developing cerebral cortex have hallmark gene expression signatures. Dynamics in gene expression define NSC, BP, and NBN heterogeneity, changes in signaling potential, and transcription factor activity. Shifts in transcriptional space over developmental time correspond to neural progenitor fate commitment. Signaling pathways and transcriptional networks during cortical development identify functional nodes and novel gene signatures, implying a 'cellular logic' to fundamental cell fate decisions. Abstract : An atlas of mouse cerebral cortical cell transcriptome during development reveal patterns of gene expression that correspond to cell fate decisions.